(untitled) - Creech, Bill (New York, 1994)
Creech, a retired U.S. Air Force general, argues persuasively that in order to remain competitive and combat Japanese incursions into U.S. markets, corporate America must adopt the five principles of total quality management (TQM): product, process, organization, leadership and commitment. In this sensible study, consultant Creech explains how non-statisticians can comprehend and apply TQM methods, which require a humanistic orientation, empowerment on all levels and a holistic approach that involves the entire organization. TQM's decentralization calls for an emphasis on teams that serves as an antidote to the stultifying effects of centralized control. Creech maintains that TQM is best understood in the light of the writings of Peter Drucker, W. Edwards Deming and Joseph Juran, whose work is viewed "by the Japanese to be mainly responsible for the economic recovery of their country after World War II." Numerous detailed corporate and military case studies enrich this comprehensive, often persuasive brief.
Keywords: Total quality management; United states